TECHNO-PUBLIC RHETORIC, SPECULATIVE VALUE, AND THE GROWTH OF ALT-TECH DIGITAL MEDIA COMPANIES - Van Schenck, Reed (AoIR Selected Papers of Internet Research, 2026)
Despite the growth of reactionary networks, the "alt-tech" platforms built to host their content have failed to make a profit. Nevertheless, investors continue purchasing shares in alt-tech firms, enabling them to grow. This paper contends that, in order to understand the economic and ideological trends driving the growth of alt-tech platforms, Internet studies must rupture from traditional understandings of value and apprehend speculative value, or the social currency assigned to a platform's products, assets, and mission as they are assumed to appreciate over time. Through rhetorical criticism of financial, corporate, and investor-relations communications of five alt-tech firms (Gab, Rumble, Telegram, Trump Media & Technology Group, and X), this paper identifies a rhetoric of techno-publicity through which reactionary digital platforms solicit investiture. Techno-publicity posits privately-owned platforms as ideal mediators for democratic discourse, securing their speculative value. I identify three discursive pillars present in alt-tech financial statements: a) transgressive individualism, which states that digital infrastructure is best stewarded by entrepreneurs; b) digital producerism, which holds that technical expertise is the only requisite skill for mediating healthy publics; and c) network fetishism, which characterizes platformed user networks as decentralized and thus the surest mediator of public discourse. These discourses project the alt-tech firm into the future as an ideal steward of digital democracy by imbuing investor confidence in the figure of the CEO and the values of cyber-libertarianism. I conclude by situating techno-public rhetoric within the business model of all social media platforms, alt-tech or otherwise, elucidating the ongoing backslide in platform governance.